Entrenamiento sobre Trips, BMS, Observatorio del Frijol, procesamiento industrial, cadena de valor, perfil del producto, sistemas alimentarios, y modelos de negocio socios del proyecto del frijol KoLFACI semestre II. Septiembre, 2025 Palmira, Colombia - Gomez Jimenez, Maria Isabel; Wilker, Jennifer Leanne; Buendia Castellanos, Hector Fabio; Guerrero Rodriguez, Alberto Fabio; Rivera, Tatiana; Hurtado, Jhon Jairo; Gallego Castillo, Sonia; Andrade, Robert; Pedreros, Ricardo; Vergara, Jose Daniel; Blanco Garcia, Maria Alejandra; Garcia, Carolina; et al. (2025)
During the second semester (September-October) of 2025, a series of training activities was conducted under the KoLFACI project, aimed at strengthening the technical capacities of partners in research, plant breeding, technological innovation, and strategic decision-making for common bean production in Latin America.